Milk clotting activity and production of bioactive peptides from whey using Maclura pomifera proteases - Corrons, María Alicia (2012)
A crude extract named pomiferin was obtained from latex of fruits of Maclura pomifera (Raf.) Schneid (Moraceae), containing serine endopeptidases. The caseinolytic activity was 14.1 +/_ 0.8 Ucas/mL and the protein concentration was 1.5 +/- 0.1 mg/mL. Isoelectrofocusing of pomiferin followed by zymogram analysis showed several bands (pI 3.7 - 9.2) of which those of pI  6.0 had a high proteolytic activity. The highest esterase activity was achieved on Ala, Gly and Leu derivatives of N-alfa-CBZ-pnitrophenyl amino acid esters. In milk clotting assays pomiferin showed a clotting strenght similar to that of chymosin standard (50 IMCU/mL), and clots presented stable consistency over time. A linear dependence was presented between the clotting time and the enzyme dilution.Clotting activity had increased significantly until 25 mmol/L of CaCl2 content. Wheys obtained using pomiferin and chymosin as clotting agents showed specific peptide profiles on tricine SDS-PAGE gels. Antioxidant activity and ACE inhibitory activity of filtered whey obtained with pomiferin were 57.4 +/- 0.4 % and 11 +/- 2 %, respectively. Both activities could be attributed to small peptides generated by action of proteases on milk proteins during clotting, therefore this whey could be used as ingredient in the manufacture of functional foods.